Research Progress on Resistance and Mechanisms of c-Met Inhibitors in Treating MET Exon 14 Skipping Mutant Non-Small Cell Lung Cancer - Bu, Yijie; Song, Wenpeng; Wang, Yan; Che, Guowei (Journal of Thoracic Disease, 2026)
Background and Objective: and Objective: MET exon 14 skipping mutation is a significant driver alteration in non-small cell lung cancer (NSCLC). c-Met inhibitors have emerged as a pivotal therapeutic option for targeting this mutation, demonstrating significant efficacy in improving overall survival and patient outcomes. However, the development of resistance to these inhibitors is inevitable. This review aims to summarize the current landscape of c-Met inhibitors in treating NSCLC with MET exon 14 skipping mutations and to delineate the emerging challenge of drug resistance. Based on existing research evidence, we elaborate on the underlying mechanisms of resistance, with the goal of informing personalized treatment strategies and providing a foundation for future research aimed at overcoming this resistance.Methods: A literature review was conducted using terms related to the treatment of c-Met inhibitors in MET exon 14 skipping NSCLC and mechanisms of resistance. Predefined inclusion or exclusion criteria were not applied, and articles that contained clinical trials, retrospective studies, in vitro experiments and meta-analyses published in English mainly within the last 10 years were selected.Key Content and Findings: Key Content and In this review, we briefly describe the MET signaling pathway and the MET exon 14 skipping mutation, introduce the efficacy of major c-Met inhibitors in clinical practice, and discuss the main mechanisms of drug resistance, including primary and acquired resistance.Conclusions: The application of c-Met inhibitors has revolutionized the treatment of NSCLC harboring MET exon 14 skipping mutations, substantially improving patient outcomes. However, drug resistance comprising primary and acquired mechanisms poses a major clinical challenge. Current understanding of these resistance mechanisms remains limited. Future research is warranted to further elucidate resistance and to optimize therapeutic strategies, thereby enhancing efficacy and survival benefits for these patients.